Quality of nursing care and nurses' working environment in Ethiopia: Nurses' and physicians' perception - Abate Yeshidinber Weldetsadik; Teshome Gishu; Atnafu Mekonnen Tekleab; Yemisrach Mekonnen Asfaw; Tesfaye Girma Legesse; Tangute Demas (Elsevier, 2019)
Background: Nurses play critical roles as patient advocate, regulating quality of care and improve health care values. Data are scarce regarding quality of nursing care in Ethiopia. Objective: To assess quality of nursing care and convenience of the nurse working environment to provide quality of nursing care in a tertiary hospital in Ethiopia. Methods: Data was collected prospectively using Quality of Nursing Care Questionnaires of Safford & Schlotfeldt and Practice Environment Scale of Nursing Work Index (PES-NWI). One hundred seventeen nurses and 51 physicians were included and data was analyzed using SPSS for windows version-20. Result: Four of the five PES-NWI variables had mean score less than 2.5, suggesting the nursing environment and management was unfavorable to assure quality care. All nursing care performances were low. The highest score was in nurse carryout orders (66.7%) and lowest in nurse-physician collaboration (24.8%). Conclusion: The quality of nursing care is substandard. Favorable environment and nurse physician relationship must be established to provide quality care. Keywords: Quality-nursing care, Perception, Physician, Nurse work-environment, Ethiopia